Pelaksanaan Supervisi Akademik Oleh Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru - Somantri, Manap; Dina Yuriza Putri; Sumarsih (Manajer Pendididikan, 2023)
The aim of the research is to describe academic supervision in increasing teacher professionalism in Rembas 1 Public Junior High School, Musirawas Regency. The research method uses a qualitative approach. The research subjects were school principals, vice principals and teachers. Collecting data with observation techniques, interviews and documentation. Data analysis techniques include data reduction, data presentation and data verification. The results of the study: 1) the implementation of programmed supervision can improve the professional abilities of teachers in planning and implementing learning, 2) school principals use more group supervision techniques with meetings, workshops, 3) the supporting factors are the teacher's positive attitude and response, while the obstacles are: Busyness school principals, limitations of learning media.